TOPICALITIES AND MECHANISMS FOR ASSURING QUALITY OF BORDER GUARDS' PROFESSIONAL TRAINING - Zalitis, Ivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The topicality of the research is determined by the present day challenges within the frame of the EU border security field and space of professional education, which directly project onto the quality requirements for professional training of employees of Latvian law enforcement institutions.Research aim: on the basis of the analysis of quality management aspects during the educational process of professional training in law enforcement education institutions of the Baltic countries, to develop and approbate a model for establishing the basic principles of creating quality management systems (QMS) and methodology of the use of this model; to determine the most topical and effective basic principles of developing QMS in education establishments of law enforcement institutions. To achieve the aims of a quantitative-qualitative research, the theoretical (analysis) and empirical (data collection, synthesis and modelling, data processing) methods have been applied. Research results: a) the main problems in the field of quality management of border-guard professional training have been identified and recommendations for their solution have been put forward; b) the model, methodology and instruments for a practical application of the model have been approbated; c) the most topical basic principles of developing QMS in education establishments of law enforcement institutions have been formulated. The scientific novelty of the research lies in the conceptual understanding of competencies for quality assurance of border guard professional training as well as in creating a model for establishing the most effective basic principles of developing QMS in education institutions.